Determinants of drug knowledge, attitudes and practices of MSU-Iligan Institute of Technology High School students - Salazar, Milagros R. (Milagros Ramos) 1942-
Identification of some of the factors which affect individual knowledge, attitudes and practices concerning drugs was done in this study. It aims to determine the nature and extent of the knowledge, attitudes and practices concerning drugs among high school students of MSU-IIT, the factors related to the drug knowledge, attitudes and practices of the students, and the factors which best predict the students' attitudes and practices concerning drugs. It was found in this study that the students' knowledge on drugs is limited but their attitudes and practices concerning drugs are favorable.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Drugs and youth -- Philippines; Drug abuse -- Philippines; Iligan City; Iligan City